RNAimmuno: A database of the nonspecific immunological effects of RNA interference and microRNA reagents - Olejniczak, Marta (Cold Spring Harbor Laboratory Press, 2012)
The RNAimmuno database was created to provide easy access to information regarding the nonspecific effects generated in cells by RNA interference triggers and microRNA regulators. Various RNAi and microRNA reagents, which differ in length and structure, often cause non-sequence-specific immune responses, in addition to triggering the intended sequence-specific effects. The activation of the cellular sensors of foreign RNA or DNA may lead to the induction of type I interferon and proinflammatory cytokine release. Subsequent changes in the cellular transcriptome and proteome may result in adverse effects, including cell death during therapeutic treatments or the misinterpretation of experimental results in research applications. The manually curated RNAimmuno database gathers the majority of the published data regarding the immunological side effects that are caused in investigated cell lines, tissues, and model organisms by different reagents. The database is accessible at http://rnaimmuno.ibch.poznan.pl and may be helpful in the further application and development of RNAi- and microRNA-based technologies.